Figure - Salmon Smolt Bypass Experiment 2020 - Joacim Näslund (2590159) (2021)
Overview of the experimental flume, arenas and treatments. A) Top view and dimensions of the experimental flume. Arrows show flow direction; yellow symbols represent the ejector pumps. B) Side view perspective of the experimental arena (note that the length of the arena is not drawn to scale). C) Screen shots from cameras C1-2 (see B for placement). D) Design of the gravel bed treatment, which was placed in the passageway. E) Illustration of an Atlantic salmon (Salmo salar) smolt. Parts of this figure are derived from doi:10.6084/m9.figshare.14672676 (license CC-0).